Effect of Elevated Temperatures on Mechanical Properties of Spliced and Non-Spliced Steel Reinforcements: Experimental Study - Chanachai Thongchom; Suphanut Kongwat; Jongchai Jaitrong; Suraparb Keawsawasvong; Linh Van Hong Bui; Boonchai Stitmannaithum; Saeed Mousa (Buildings, 2023)
Steel reinforcement is an essential part of reinforced concrete, providing structural strength. In case of fire, the steel reinforcement severely loses its mechanical properties, leading to structural collapse in some elevated temperatures. Thus, this work mainly investigates the mechanical properties of spliced and non-spliced steel reinforcements after being exposed to 500 °C, 700 °C, and 900 °C. The results show that the mechanical properties of steel reinforcements significantly change after exposure to temperatures exceeding 500 °C, and the diameter of steel reinforcements does not considerably affect post-fire properties. The proposed equations from previous work were also compared to the testing results in terms of post-fire stress–strain curves and mechanical properties, resulting in overestimation at temperatures of 700 °C and 900 °C. The study finds that using a mechanical coupler has the potential to increase the residual yield strength at a temperature of 500 °C, but it lacks post-fire elongation at a temperature of 700 °C due to observed failure behavior after testing. Furthermore, the failure occurred at the mechanical couplers when the exposure temperature reached 700 °C. The modulus of elasticity of non-splices was the most critical parameter, which was maximally different by 23.9% compared to non-spliced steel reinforcements.